(ENT300) Fundamental of entrepreneurship: Hello baby childcare / Nurain Hosain... [et.al] - Hosain, Nurain; Abang Hassan, Dayang Rabi’atul Adawiyah; Mohd Idrus, Wan Syafiqah Amirah; Omar, Siti Nur Dahlia; Alias, Nurfatin Anisa (2016)
The name of our company is Hello Baby Childcare. Our business is based on childcare for children ages 2-4. We provide food for each of the children. We prepare food three times a day that is Breakfast start from 8.00 am-6.00pm. We also provide a playground for a kids. For the Industry profile, our business is owned actively by partnership, incoperated as an Hello Baby Childcare. We recognize the limitation of attempting to manufacture our business in small premise. So that, our companies can more concentrate on childcare at some place only. We give good services based on our customer demand.